Upaya Peningkatan Ketepatan Shooting Flying Jump Shoot pada Atlet Bolatangan ABTI Kota Kediri melalui Permainan Target - Mokhammad Firdaus; M Nurkholis; M. Anis Zawawi; Ardhi Mardiyanto Indra Purnomo (SPRINTER: Jurnal Ilmu Olahraga, 2025)
The purpose of this study was to determine the improvement of jumpshoot shooting ability in handball games in ABTI Kediri City athletes. Through this study, it is expected to obtain accurate data on how much jump shoot shooting ability has increased through target games. This research method uses a descriptive statistical approach. The sampling technique used was total sampling, while data collection was carried out by testing jump shoot shooting abilities with target games and measurement tests. From these results, it was concluded that target training has a significant influence on the accuracy of handball athletes' flying shots. To determine the effect of target training, the average and the difference between the post-test and pre-test scores can be seen in the table above. It appears that the post-test score has a higher average than the pre-test score (66.96 > 53.16) with a difference of 13.8. Based on the description above, it shows that target training has an effect in the form of increasing the accuracy of flying shots in ABTI handball athletes in Kediri City. One of the effective shooting techniques for scoring goals in handball is the flying jump shoot. This shooting technique movement is carried out by the player jumping, then shooting or throwing the ball at the goal as hard as possible in order to score a goal. The results of the study concluded that the flying jump shoot is known to have a higher goal percentage than the standing throw shoot technique.